A Business Feasibility Analysis on Mitra Tahuta in Gowa District - Sitti Hajerah Hasyim; Nurjannah Nurjannah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
One of the contributors to the Indonesian economy comes from the processing industry sector, such as the tofu making business. The purpose of this study was to determine the business feasibility of Mitra Tahuta in Bajeng District, Gowa Regency. The data collection method used is a combination of quantitative and qualitative methods using data analysis, namely (1) profit/profit theory approach, (2) break-even analysis, (3) production cost analysis, and (4) ratio analysis. The results of this study indicate that (1) the average profit of tofu production in Mitra Tahuta is IDR 25.200.000 per production, (2) the Net Benefit Cost Ratio shows positive net benefits that are greater than negative net benefits, (3) Tofu Enterprises in Mitra Tahuta, Bajeng District, Gowa Regency deserves to be a business so it must be developed.